A mixed methods study of the healthcare received by patients diagnosed with a personality disorder on acute general hospital wards. (17th February 2021) - Sharda, Leila; Baker, John; Cahill, Jane
Abstract: Aim: The study examined concurrent mental and physical healthcare received by patients diagnosed with a personality disorder on acute general hospital wards. The specific objectives were (i) to conduct a web based cross sectional survey and (ii) to explore experiences and perspectives with a subsection of the survey sample, using telephone interviews. Design: A convergent parallel mixed methods design, which comprised a web‐based cross sectional survey ( n = 65) with embedded qualitative telephone interviews ( n = 12). Participants were social media users, with a self‐reported diagnosis of personality disorder, admitted to an acute general hospital in the UK in the previous 2 years. Methods: Participants were recruited on social media between May 2017 and August 2017 by snowballing. Mixed data were integrated at the stage of analysis using a framework approach. Findings are reported thematically. Results: Most of the participants surveyed (94%, n = 61) reported distress during admission to the acute general hospital. However, the findings indicated the hospital environment was not conducive to mental health. Four interrelated themes were identified and related to: patient distress; the workforce; service delivery; and service design. Conclusion: Findings indicated that patients with a personality disorder diagnosis received disadvantaged healthcare, might be at considerable risk of treatment noncompletion, and were languishing in the gaps between mental and physical health services. Impact: This is one of the first studies to collect primary data on the concurrent mental and physical healthcare received by patients diagnosed with a personality disorder on acute general hospital wards. Ad hoc training and education focused on raising awareness of 'personality disorder' would not seem sufficient to address the deficits. This research may be of interest to people who use mental health services, acute general hospital and liaison clinicians, hospital managers and researchers. 摘要: 目的: 本研究期限内, 已对急症全科医院病房中获诊断为人格障碍的患者同时接受的精神和身体护理进行核查。具体目标包括 (i) 开展基于网络的横断面调查和 (ii) 通过电话访谈, 探索调查样本人员的部分经验和观点。 设计: 一项收敛并行混合方法设计, 包括基于网络的横断面调查 ( n =65) 和嵌入式定性电话访谈 ( n =12) 。参与者均为社交媒体用户, 自我报告获诊断为人格障碍, 且在过去的两年内被英国的一家急症全科医院收治。 方法: 参与者是通过滚雪球的方式在社交媒体上招募, 招募时间为2017年5月至2017年8月。应在分析阶段使用框架法, 以便对混合数据进行整合。调查结果应按主题报告。 结果: 大多数调查者 (94%, n =61) 报告称, 其在急症全科医院住院期间感到痛苦。然而, 调查结果显示, 医院环境可能对心理健康造成不利影响。现已确定四个相互关联的主题, 分别是: 患者痛苦、劳动力、服务提供和服务设计。 结论: 研究结果表明, 获诊断为人格障碍的患者曾接受不利的健康护理, 极大可能面临治疗不完整的风险, 所接受的精神和身体健康服务不对等, 因此饱受折磨。 影响: 此为首批收集急症全科医院病房中获诊断为人格障碍的患者同时接受的精神和身体护理原始数据的研究之一。尽管已经开展以提高"人格障碍"意识为重点的特殊培训和教育, 上述缺陷仍然无法解决。 本研究可能引起精神健康服务接受者、急症全科医院、联络临床医师、医院管理人员和研究人员的高度关注。